Features of the pathogenesis and course of myocardial infarction in COVID-19 patients: a descriptive review - M. G. Chashchin; A. Yu. Gorshkov; A. V. Strelkova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2022)
The coronavirus disease 2019 (COVID-19) pandemic remains one of the most urgent problems for healthcare professionals due to the variety of non-pulmonary manifestations. Along with the respiratory syndrome in a significant proportion of patients, the disease course is accompanied by pronounced systemic inflammatory response and hemostasis changes. This is associated with a high risk of complications, especially in patients with concomitant cardiovascular pathology. The aim of the study was to analyze and systematize the literature data on the pathogenesis, clinical course, and outcomes of myocardial infarction (MI) in patients with COVID-19. For review, publications indexed in the PubMed, Google Scholar, Web of Science, and Cyberleninka databases were used. The search depth was 2 years, starting from 2020. The review is based on summarized data from the most relevant clinical studies, reports and systematic reviews. The literature analysis made it possible to conclude that the published data on MI in patients with COVID-19 are currently contradictory. Multiple thrombosis, sepsis, macrophage activation, increasing hypoxemia, imbalance between myocardial oxygen supply and demand in patients with severe COVID-19 have led to a high incidence of type 1 and type 2 MI. It should be especially noted that in a number of cases, MI with COVID-19 occurs in patients with intact coronary arteries, and its course is associated with a high incidence of complications, which, in turn, leads to a significant increase in short- and mid-term mortality.